Flexibility assessment of a biorefinery distillation train: Optimal design under uncertain conditions. (12th July 2020) - Di Pretoro, Alessandro; Montastruc, Ludovic; Manenti, Flavio; Joulia, Xavier
Highlights: Distillation feasibility boundaries can be a priori determined by mean of an accurate thermodynamic analysis via residue curve maps. Since indexes assess different properties, in order to carry out a reliable flexibility assessment, the most suitable one should be identified according to the expected deviation nature. The higher flexibility of a process design is not sufficient to provide its final validation until its higher profitability is proved as well. Abstract: Multicomponent mixtures can be separated into their single components by mean of different distillation system configurations. The typical distillation train design procedure consists of the assessment of the optimal columns configuration according to the economic and operational aspects. However, this optimal design is strictly related to the operating conditions, i.e. perturbations, when present, can seriously compromise the operation profitability. In these cases a flexibility analysis could be of critical importance to assess the operating conditions range of better performance for different system configurations. This is the typical case of biorefineries where the floating nature of the feedstock causes composition disturbances downstream the fermenter across the year's seasons. A brand new ABE/W mixture separation case study has been set up; this mixture derives from an upstream microbial conversion process and the successful recovery of at least biobutanol and acetone is crucial for the return on the investments. This paper then compares the possible distillation train configurations from a flexibility point of view. The analysis is focused in particular in highlighting the differences, if present, between the economic optimal solution and flexibility optimal configuration that could not be the same, causing this way a very profitable design to be much less performant under perturbated conditions. Furthermore, a detailed analysis correlating the complex thermodynamics to the operation under uncertain conditions is thoroughly discussed. The proposed design procedure allowed to highlight the differences between weak and strong flexibility constraints and resulted in a dedicated "additional costs vs. flexibility" trend useful to improve the decision making.